Komitmen organisasional melalui evaluasi inti diri, dukungan sosial, dan motivasi - Rony Setiawan; Ariesya Aprillia (Jurnal Manajemen Maranatha, 2022)
Humans are main actors in achieving organizational success. Every institution seems to be forced to adapt to changes due to the pandemic. The current situation requires that every aspect of employee life in almost every industry is carried out online, including education corporations. Campus Z faces extra challenges as a well-known private university to consistently demonstrate excellent transformational service performance. In achieving an excellent organization, various collaborations of qualified resources are needed, one of which is the ownership of administrative staffs who are highly dedicated to the organization. The positive attitude of employees is determined by the quality of their perspective on themselves and their assessment of their work and organization enviroment. By collecting data through a context review and Google Forms, the research team wanted to analyze the relationship between core self-evaluation, social support, extrinsic motivation, and intrinsic motivation as determinants of organizational commitment. Through multiple linear regression analysis, it has been proven that organizational commitment is positively influenced by extrinsic motivation and negatively influenced by intrinsic motivation. The research team hopes that the results of this study can provide constructive feedback on the leadership and management development of Campus Z in the long term.